Positive observation of the 209 Dido asteroidal occultation of March 10, 2005 - CORELLI, PAOLO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2005)
Observation methods, data collection and the following processing techniques, related to the positive observation of the 209 Dido asteroidal occultation recoded from Mandi Observatory – Pagnacco, Italy on March 10th 2005 are reported. The observation has been planned within a European program managed by EAON (European Asteroidal Occultation Network) with the purpose of increasing the knowledge of the shape of these objects as well as of their orbits. In some lucky cases (not in this) it has been possibile to detect a minor object orbiting around the main asteroid, whose existence was unknown so far.